PANDEMIC CRISIS AND FINTECH - MALAYSIAN EVIDENCE - Puteh Salin, Ahmad Saiful Azlin; Che Hasan, Haslinawati; Nik Kamarudin, Nik Nurul Aswani; Mad, Salina (I-iECONS e-proceedings, 2023)
The recent pandemic crisis that occurred across the globe has changed the way human lives including the use of information and communication technologies (ICT). However, the adoption of technology due to the crisis in financial function is still under research, knowing that Malaysia is an emerging country that still lag behind in responding to Industrial Revolution 4.0. Thus, the purpose of this study is to examine the current state of technology adoption by the finance professional and their determinants to adopt technology, specifically financial technology (Fintech) in the workplace. To achieve these purposes, questionnaires were distributed online to collect the information. It comprises three sections namely demographic information, information on respondents’ experience and knowledge on Fintech and finally the factors that affect users’ intention to use Fintech. This research adopted the Unified Theory of Acceptance and Use of Technology (UTAUT) theoretical framework as a theoretical foundation of the study. The findings showed that while the respondents are considered as highly experienced and heavy technology users, they have a moderate knowledge of technology. In addition, performance expectancy, behavioral intention and attitude are the biggest influence for them to adopt Fintech in the workplace. This finding shows that many finance professionals in Malaysia do not refuse to revolutionize their work process by transforming their job tools from manual-based to computerized operation and use more sophisticated devices.